1991
DOI: 10.1038/eye.1991.126
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in proliferative vitreoretinopathy

Abstract: SummaryThis study determined the presence of interleukin 1 (IL-l), interleukin 6 (IL-6), tumour necrosis factor ex (TNFex), tumour necrosis factor � (TNF�), interferon y (IFNy), transforming growth factor �2 (TGF�2) and fibroblast proliferation activity (FPA) in vitreous aspirates from eyes undergoing vitrectomy for the treatment of ret inal detachment complicated by proliferative vitreoretinopathy (PVR) or uncom plicated retinal detachment (RD). Cadaveric vitreous from normal subjects were used as controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 17 publications
(1 reference statement)
1
120
2
1
Order By: Relevance
“…Several studies have addressed the recent hypothesis that the reduced angiogenesis of PDR is due to the release of growth factors and interleukins from the ischaemic retina. [12][13][14][15][16] Abnormal production of Table 1 The levels of IL-1b and TNF-a in patients with PDR and controls…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed the recent hypothesis that the reduced angiogenesis of PDR is due to the release of growth factors and interleukins from the ischaemic retina. [12][13][14][15][16] Abnormal production of Table 1 The levels of IL-1b and TNF-a in patients with PDR and controls…”
Section: Discussionmentioning
confidence: 99%
“…15,21 Studies of vitreous and serum IL-1b concentrations in patients with proliferative vitreoretinopathy (PVR) and PDR have come to different conclusions. 14,22,23 Kaufmann et al 23 showed an increased vitreous IL-6 in 29% of patients with PDR, but did not detect any IL-1b.…”
Section: Tnf-α_vmentioning
confidence: 97%
“…Growth factors such as basic FGF can partially rescue retinal degeneration; however, the growth stimulatory effects on other cell types are problematic. 7,8,[10][11][12]30 Although further studies are necessary, in the light of our observations, we believe TFPI-2 can be utilized without such adverse effects in the treatment of retinal degeneration. Quantitative analysis revealed that the ONL thickness in the rTFPI-2-treated eyes was significantly more than the control eyes (Mann-Whitney U test; P ¼ 0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the retinal degeneration in an animal model is partly rescued by several growth factors, including basic fibroblast growth factor (bFGF), presumably by inhibiting the apoptotic process. 1,2 However, these factors stimulate proliferation of fibroblast 3 and vascular endothelial cells, 4 and are involved in detrimental processes such as proliferative vitreoretinopathy [5][6][7][8] and preretinal or subretinal neovascularization, [9][10][11][12] suggesting that other compounds without the adverse effect of fibroblast or endothelial growth are necessary to achieve the establishment of pharmaceutical therapy for the retinal degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is a complex process comprised of events that are similar to those of the wound healing response with inflammation, migration and proliferation of a variety of cells. [3][4][5] These membranes can exert traction and reopen previously closed retinal breaks, create new breaks, and distort or obscure the macula.…”
mentioning
confidence: 99%